EUROPEAN SILVER PAPER ON THE FUTURE OF HEALTH PROMOTION AND PREVENTIVE ACTIONS, BASIC RESEARCH, AND CLINICAL ASPECTS OF AGE-RELATED DISEASE - Belgische Vereniging voor Gerontologie en Geriatrie, - (Tijdschrift voor Gerontologie en Geriatrie, 2023)
Besluit European Summit, Wroclaw, september 2008